The Lisbon stock exchange in the twentieth century - Maria Eugénia Mata (Investigação, 2017)
This book addresses both domestic and foreign readers, and for thatreason appears in English. Following the survey of history of the LisbonExchange published in 1996 by David Justino, the present text extendsthat medieval period to the Nineteenth century analysis to the presentday. Many other Stock Exchanges in Europe and elsewhere have beenstudied and published by many authors, but no comparable book forPortugal has existed until the present work. The text is accessible tomedium-knowledge readers. In a world of internationalization ofcorporations and financial institutions it is paramount that they beable to mobilize the capacities of the Capital Market to finance theeconomy,and to possess a thorough understanding of the role of a Stock Exchangefor the efficient working of that market. Portugal is a case of greatinterest to developing countries, as it was able to re-instate themarket after 1974, and with such success that the country joined theEuropean Union in 1986 and the innovative Euronext Group of StockExchanges in 2002. The book discloses for the first time a database usedto calculate a share index that was developed over three years with thehelp of the FCT grant PTDC/HISHIS/100132/2008, and using a methodologythat makes that index comparable to common international indices andcompatible with the General Index computeddaily by the Exchange.